2018
DOI: 10.1161/jaha.117.007987
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Antagonism in Patients With Atrial Fibrillation: Findings From the ORBIT‐AF (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation) Registry

Abstract: BackgroundMineralocorticoid receptor antagonist (MRA) therapy may be beneficial to patients with atrial fibrillation (AF), but little is known about their use in patients with AF and subsequent outcomes.Methods and ResultsIn order to better understand MRA use and subsequent outcomes, we performed a retrospective cohort study of the contemporary ORBIT‐AF (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation) registry. AF progression and cardiovascular outcomes were compared using propensity‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The current study provides clinically relevant evidence from an extreme state of hyperaldosteronism that using MR antagonists to adequately block the MR, or removal of the unilateral source of aldosterone excess via surgical adrenalectomy, may mitigate the excess risk for atrial fibrillation attributed to pathologic MR activation. These findings are in agreement with recent studies in essential hypertension and heart failure, which suggest that blockade of the MR may be a potential target for preventing or delaying the incidence of atrial fibrillation and stroke. Our findings may also help contextualize prior studies in cohorts with PA that did not include an evaluation of physiological biomarkers of MR blockade and observed that lifelong MR antagonist therapy did not lower the risk for atrial fibrillation, whereas surgical adrenalectomy did …”
Section: Discussionmentioning
confidence: 99%
“…The current study provides clinically relevant evidence from an extreme state of hyperaldosteronism that using MR antagonists to adequately block the MR, or removal of the unilateral source of aldosterone excess via surgical adrenalectomy, may mitigate the excess risk for atrial fibrillation attributed to pathologic MR activation. These findings are in agreement with recent studies in essential hypertension and heart failure, which suggest that blockade of the MR may be a potential target for preventing or delaying the incidence of atrial fibrillation and stroke. Our findings may also help contextualize prior studies in cohorts with PA that did not include an evaluation of physiological biomarkers of MR blockade and observed that lifelong MR antagonist therapy did not lower the risk for atrial fibrillation, whereas surgical adrenalectomy did …”
Section: Discussionmentioning
confidence: 99%
“…However, up‐titration of guideline‐recommended treatments or dosing of diuretics during the TIM‐HF2 trial were similar in the AF and SR patients, both groups in the RPM trial arm received a similar number of cardiac medication changes by a TMC physician during the trial. Previous subgroup analyses of AF patients showed differences between groups with regard to RAAS inhibitors, neprilysin inhibition, beta blocker therapy, mineraloreceptor antagonists, and SGLT2‐inhibition 25–27 . Differences in the pharmacotherapy therefore appear unlikely to explain the profound benefit for AF patients randomized to RPM.…”
Section: Discussionmentioning
confidence: 98%
“…Previous subgroup analyses of AF patients showed differences between groups with regard to RAAS inhibitors, neprilysin inhibition, beta blocker therapy, mineraloreceptor antagonists, and SGLT2inhibition. [25][26][27] Differences in the pharmacotherapy therefore appear unlikely to explain the profound benefit for AF patients randomized to RPM.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, a reduction in mortality and morbidity was registered. Additional clinical benefits of MR antagonists were reported in patients with left ventricular hypertrophy and hypertension (Pitt et al, 2003) and in patients with atrial fibrillation (Dabrowski et al, 2010;Fudim et al, 2018). For patients with heart failure with preserved ejection fraction, the picture is less clear with no significant reduction in the primary composite outcome of death due to cardiovascular causes or hospitalization (Pitt et al, 2014).…”
Section: Cardiovascular Effects Of Mineralocorticoid Receptor and Agingmentioning
confidence: 99%